Analysis Of Drug Logistics Planning Management In Community Health Centers New Pakuan Of Jambi City - Siti Aisah; Adila Solida; Arnild Augina Mekarisce; Rumita Ena Sari (International Journal of Health Engineering and Technology, 2026)
Drug logistics planning in primary healthcare centers remains a major challenge in ensuring medicine availability and continuity of health services. Inadequate planning often leads to stockouts, overstock, and mismatches between drug supply and patient needs. This study aimed to analyze the implementation of drug logistics planning management at Pakuan Baru Public Health Center, Jambi City. This research used a qualitative observational design with a case study approach. The population consisted of all personnel involved in drug logistics planning, while seven informants were selected using purposive sampling. Data were collected through semi-structured interviews, observation checklists, and document review of LPLPO, stock cards, and planning reports. Data analysis employed the Miles and Huberman model through data reduction, data display, and conclusion drawing with triangulation techniques. The results showed that drug planning was conducted through stages of drug selection, consumption compilation, calculation of drug needs, projection, and procurement adjustment based on LPLPO data, National Formulary, and consumption methods. However, several obstacles were identified, including distribution delays, mismatches between proposed and received drugs, limited budgets, and recurring stock shortages. In conclusion, drug logistics planning management at the health center has generally followed national guidelines, but improvements in data based planning, distribution systems, and monitoring are still required to optimize drug availability and service continuity.